Advanced particle swarm optimization for efficient coordination of distributed generators in power distribution networks - Funso Kehinde Ariyo; Ayooluwa Peter Adeagbo; Oludamilare Bode Adewuyi; Samson Oladayo Ayanlade; Tayo Uthman Badrudeen (Journal of Electrical Systems and Information Technology)
Abstract Integrating distributed generators (DGs) into electrical power networks remains a significant area of research which has several technical and economic benefits for optimum performance, especially at the distribution level. This study presents a model of power distribution networks with renewable distributed generation (DG) units. It adapted Loss Sensitivity Factor (LSF) and Constriction Coefficient Particle Swarm Optimization (CCPSO) technique to ascertain the optimal placement and sizing of the DG units. The numerical analysis is executed on the Imalefalafia 32-bus network which is a real distribution network in Nigeria and the commonly known standard IEEE 33-bus network. The result shows that the scenario where cost minimization with loss reduction and voltage stability improvement concurrently performs better than other scenarios for different numbers of allocated DGs. With 3 DGs incorporation, the real and reactive power loss reduction of 62.46% and 62.32%, respectively, were achieved in scenario three compared to 14.06% and 14.46% in scenario two and 61.48% and 61.46% in scenario one for IEEE 33-bus RDN while for Imalefalafia 32-bus, the real and reactive power loss were reduced by 71.07% and 71.13% were achieved in scenario three compared to 43.95% and 43.99% in scenario two and 55.87% and 55.92% in scenario one. It was also observed that the voltage at the worst performing bus improves significantly better for scenario 3 for all numbers of DGs compared to the other scenarios.